Design of educational programs for preschool education using the example of integration of the compulsory part and the partial program for the early physical development of children - Paramonova M.Yu.; Tolkacheva G.N.; Volobueva L.M.; Nikiforova O.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop algorithms for designing educational programs for preschool education using the example of the integration of the compulsory part (FEP DE) and a partial program for the early physical development of children. Methods and structure of the study. The structure and content of the educational program of preschool education have been developed, partial programs have been analyzed, including those for the early physical development of children, algorithms for integrating two parts of the educational program have been determined, and a designer of educational programs for preschool education (hereinafter referred to as the Constructor) has been created. Results and conclusions. A Constructor has been developed for creating educational programs for preschool educational organizations, which includes in its structure a mandatory part represented by the Federal program and a part formed by participants in educational relations (PFP). The constructor was created in the form of a chat bot in the Telegram channel, a link to it is posted on the official website of the Federal State Budgetary Institution “Institute of Child Development, Health and Adaptation” and the website “constructordo.rf”. It allows educational organizations to design an educational program by consistently answering the proposed questions. Algorithms for integrating two parts of the educational program are characterized: the inclusion in the PFP of one or more partial programs, program elements (tasks, technologies, forms of work, etc.) that expand or complement the tasks of teaching, raising and developing children from two months to seven years, presented in Federal educational program for preschool education. Recommendations for their use. The results of the study can be used in the design of educational programs of preschool educational organizations; conducting an internal audit of the compliance of educational programs with the Federal educational program of preschool education; advanced training of teaching staff in the field of preschool education; development of criteria for the selection of partial programs for early physical development of children for inclusion in the educational program of a preschool educational organization in the PFP, inclusion of the content of the regional component of the educational program of a preschool educational organization.